Effect of an Osmanthus fragrans Flower Beverage on the Antioxidant Activity in Healthy Individuals - 李國玉(Kuo-Yu Li); 蔡侑澄(Yu-Cheng Tsai); 洪千雅(Chien-Ya Hung) (臺灣農業化學與食品科學, 2013)
This study evaluated the ability of an Osmanthus fragrans flower beverage, high in polyphenols and antioxidants, to modulate the plasma antioxidant status in healthy subjects. The hypothesis that Osmanthus fragrans flower beverage supplementation would upregulate antioxidant parameters (ORAC, GSH, GSSG, GSH/GSSG ratio, GPx and SOD) in adults was tested. Twenty healthy volunteers were randomly assigned to receive one of the followings for 7 days: low-dose Osmanthus fragrans flower beverage (LD, brewing 1 g of dry Osmanthus fragrans flower in 1,000 mL of boiling water for 20 min), high-dose flower beverage (HD, brewing 2 g of dry Osmanthus fragrans flower in 1,000 mL of boiling water for 20 min) and control (1,000 mL of water only). The result showed a highly significant increase of plasma ORAC (35.4%, p ＜ 0.01), GSH (18.9%, p ＜ 0.01), GSH/GSSG ratio (52.7%, p ＜ 0.05), and GPx (90.7%, p ＜ 0.01) in the HD group, a significant decrease in plasma GSSG (21.9%, p ＜ 0.05), but no difference in plasma SOD activity. These results support the hypothesis that consumption of 1 cup a day of Osmanthus fragrans flower beverage for 7 days may increase the antioxidant defenses in healthy individuals.